2014
DOI: 10.1016/s2214-109x(13)70145-1
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence of age-related macular degeneration and disease burden projection for 2020 and 2040: a systematic review and meta-analysis

Abstract: National Medical Research Council, Singapore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
2,643
3
78

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 3,913 publications
(3,003 citation statements)
references
References 43 publications
34
2,643
3
78
Order By: Relevance
“…[38] In the same metaanalysis, prevalence in populations with African ancestry was lower than populations with European ancestry and closer to observed in Conceição das Crioulas. There was a greater number of subjects (5.1%) presenting atrophy of the retinal pigment epithelium, as a possible early sign of the disease.…”
Section: Discussionsupporting
confidence: 58%
“…[38] In the same metaanalysis, prevalence in populations with African ancestry was lower than populations with European ancestry and closer to observed in Conceição das Crioulas. There was a greater number of subjects (5.1%) presenting atrophy of the retinal pigment epithelium, as a possible early sign of the disease.…”
Section: Discussionsupporting
confidence: 58%
“…Basally, RPE is in close contact with Bruch’s membrane for barrier function forming an RPE-Bruch’s membrane (RPE-BM) complex. Aging and dysfunction of this system is closely linked to diseases such as age-related macular degeneration, which is the leading cause of irreversible vision loss in the developed world [1,2]. Risk factors include lifestyle factors such as physical inactivity and smoking [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…A ge-related macular degeneration is the leading cause of irreversible blindness in the developed world 1 and accounts for 5% of all blindness worldwide. 2 Humanized antibodies that inhibit vascular endothelial growth factor have been widely used clinically over the past decade after several randomized controlled trials demonstrated their benefit in improving visual outcomes in patients with neovascular agerelated macular degeneration (nAMD).…”
mentioning
confidence: 99%